Reassessment of the Spider Genus Clubiona (Aranei, Clubionidae) - Mikhailov, K.G. (Вестник зоологии, 2012)
The spider genus Clubiona Latreille, 1804 is reestablished in its traditional scope. Taxonomical characters of infrageneric groupings are discussed. Tribes within the Clubioninae sensu Wunderlich (2011) are not accepted. Diagnosis and short description of Clubiona s. l., as well as a provisional key to clubionid genera, are provided. The following synonymies are established: Epiclubiona Lohmander, 1945, syn. n.; Euryclubiona Lohmander, 1945, syn. n.; Gauroclubiona Lohmander, 1945, syn. n.; Heteroclubiona Lohmander, 1945, syn. n.; Hyloclubiona Lohmander, 1945 syn. n.; Microclubiona Lohmander, 1945, syn. n.; Porrhoclubiona Lohmander, 1945, syn. n.; Anaclubiona Ono, 2010, syn. n.; Breviclubiona Wunderlich, 2011, syn. n.; Marmorclubiona Wunderlich, 2011, syn. n. = Clubiona Latreille, 1804, s. l. Род пауков Clubiona Latreille, 1804 переустановлен в традиционном объёме. Обсуждаются таксономические признаки внутриродовых группировок. Трибы внутри подсемейства Clubioninae в смысле Й. Вундерлиха (2011) не принимаются. Даны диагноз и краткое описание рода Clubiona s. l., а также предварительный ключ для определения родов семейства Clubionidae, близких к роду Clubiona. Установлена новая синонимия: Epiclubiona Lohmander, 1945, syn. n.; Euryclubiona Lohmander, 1945, syn. n.; Gauroclubiona Lohmander, 1945, syn. n.; Heteroclubiona Lohmander, 1945, syn. n.; Hyloclubiona Lohmander, 1945, syn. n.; Microclubiona Lohmander, 1945, syn. n.; Porrhoclubiona Lohmander, 1945, syn. n.; Anaclubiona Ono, 2010, syn. n.; Breviclubiona Wunderlich, 2011, syn. n.; Marmorclubiona Wunderlich, 2011, syn. n. = Clubiona Latreille, 1804, s. l.